Working and corporate performance: case of Malaysia. - M. A., Zariyawati; M. N., Annuar; H., Taufiq; A.S., Abdul Rahim (2009)
Working capital always being disregard in financial decision making since it involve investment and financing in short term period. However, it is an important component in firm financial management decision. An optimal working capital management is expected to contribute positively to the creation of firm value. To reach optimal working capital management firm manager should control the trade off between profitability and liquidity accurately. The intention of this study is to examine the relationship between working capital management and firm profitability. Cash conversion cycle is used as measure of working capital management. This study is used panel data of 1628 firm-year for the period of 1996-2006 that consist of six different economic sectors which are listed in Bursa Malaysia. The coefficient results of Pooled OLS regression analysis provide a strong negative significant relationship between cash conversion cycle and firm profitability. This reveals that reducing cash conversion period results to profitability increase. Thus, in purpose to create shareholder value, firm manager should concern on shorten of cash conversion cycle till optimal level is achieved.